Researching Learning in Virtual Worlds - Peachey, Anna.; Gillen, Julia.; Livingstone, Daniel.; Smith-Robbins, Sarah. (Human-Computer Interaction Series, 2010)
Researching Learning in Virtual Worlds covers a range of research undertaken in 3D virtual environments, looking at both the methods and results of the studies. This groundbreaking book is the first to specifically address research methods and related issues for education in virtual worlds. It opens with an accessible introduction to the book and to the subject, providing an ideal springboard for those who are new to research in this area. The subsequent ten chapters present work covering a range of research methodologies across a broad discipline base, making it essential reading for advanced undergraduate or postgraduate researchers working in education in virtual worlds, and engaging background material for researchers in similar and related disciplines. Many of the chapters in this book are extended papers from Researching Learning in Virtual Environments (ReLIVE08), an international conference hosted by the Open University UK. Authors of the best papers and presentations from the conference were invited to contribute to Researching Learning in Virtual Worlds.